Sounding the Alarm: Scholarly Information and Global Information Companies in 2021 - McLean, Jaclyn; Stregger, Elizabeth (Partnership)

(untitled) (The Partnership: The Provincial and Territorial Library Associations of Canada, 2021)
Vendors and publishers collaborate and work to protect their bottom line—which is threatened by open access (OA)—by expanding into research lifecycle and data analytics, and by continuing to merge and acquire each other, reducing choice in the library market. The implementation of Seamless Access and other systems force library staff into the position of gatekeeper for systems and platforms that we have no control or input over. Vendors and publishers control the online content that libraries can access: they add and remove content at will, and classify titles according to their greatest possible sales margins, making valuable resources unavailable to libraries to license for campus-wide access. These vendor actions—which impact the research lifecycle as a whole, disrupt traditional publishing, and seek to monetize user data—are extremely concerning. Collective action is the only way to make significant inroads against these developments. We suggest some proactive ways that we can initiate these collective actions and resist these industry-wide developments imposed by vendors and publishers.